The role of organizational culture in shaping and developing job satisfaction of human resources within the organization - Rachid, Balatrache; Yassine, Mechta (The International tax journal, 2025)
This article examines the role of organizational and institutional culture in shaping and developing job satisfaction among human resources within institutions. It emphasizes that organizational culture represents the shared values and beliefs that guide employee behavior and orientations, while institutional culture provides the policies and procedures that structure work and reinforce institutional commitment. The article also discusses the transition from socialization to professional socialization, highlighting the importance of professional identities as outcomes of organizational socialization. These identities strengthen employees’ sense of belonging and help them adapt to institutional requirements. The article further highlights the role of leadership behavior and organizational communication as a bridge between organizational culture and job satisfaction. Leaders contribute by clarifying institutional values, offering support and guidance, and enhancing employees’ sense of empowerment. Meanwhile, effective organizational communication fosters positive interaction between management and employees and increases clarity regarding tasks and expectations. The article also points out that organizational loyalty consists of belonging and willingness to sacrifice, serving as an indicator of employee commitment and directly influencing overall performance and job satisfaction. In conclusion, the article affirms that strengthening organizational culture, developing professional socialization, ensuring effective leadership, and improving organizational communication are key strategies for enhancing employee satisfaction,